The Effect of Fear of COVID-19 on Destination Image, Tourist Satisfaction, and Revisit Intention: Protection Motivation Theory Perspective - Muhammad Ihwanudin; Sri Hartini Hartini; Harris Prasetya Rahmandika (LPPM Universitas Terbuka, 2023)
Purpose – This study examines the effect of fear of COVID-19, tourist satisfaction, and destination image on the revisit intention. Methodology – Data was collected through social media surveys to 370 total domestic tourist respondents. Then, the data was processed with IBM SPSS version 26 to describe demographics and SmartPLS 3.2.9 to test structural equation modelling between variables. Findings – This study showed that the fear of COVID-19 significantly affected destination image, tourist satisfaction and revisit intention. Novelty – This study has presented that health risks (COVID-19) are not a problem for domestic tourists when travelling. Thus, the threat of COVID-19 does not affect tourists' perceptions of destination image, tourist satisfaction, and revisit intention.